PENGARUH LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI - Arif, Mochamad; Purwaningrum, Desyani; Handayani, Dewi Sri; Triasningrum, Frida Widyawati (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of liquidity, solvency, and activity on financial performance in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Financial performance is measured by Return on Assets (ROA) as the dependent variable, while liquidity is measured by Current Ratio (CR), solvency by Debt to Equity Ratio (DER), and activity by Total Assets Turnover (TATO) as the independent variable. This study uses a quantitative approach using purposive sampling, so that a sample of 23 companies was obtained with a total of 69 observations over three years. The data analysis method used is multiple linear regression, preceded by a classical assumption test. The results of the study indicate that partially: (1) Liquidity has a positive and significant effect on financial performance, (2) Solvency does not have a significant effect on financial performance, and (3) Activity has a positive and significant effect on financial performance. Simultaneously, the three independent variables have a significant effect on the company's financial performance. These findings suggest that firms should maintain adequate liquidity and asset utilization efficiency to support profitability, while paying attention to their capital structure to avoid burdening financial performance. This study offers implications for corporate management and investors in making strategic decisions.